2012
DOI: 10.1534/genetics.112.144071
|View full text |Cite
|
Sign up to set email alerts
|

Limited Evidence for Classic Selective Sweeps in African Populations

Abstract: While hundreds of loci have been identified as reflecting strong-positive selection in human populations, connections between candidate loci and specific selective pressures often remain obscure. This study investigates broader patterns of selection in African populations, which are underrepresented despite their potential to offer key insights into human adaptation. We scan for hard selective sweeps using several haplotype and allele-frequency statistics with a data set of nearly 500,000 genome-wide singlenuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 83 publications
(150 reference statements)
6
50
1
1
Order By: Relevance
“…European populations, perhaps due to lesser linkage disequilibrium, as is consistent with results from previous studies [99]. Calculating disease risk and selection variation from populations within the same ancestral group might help resolve this, however it only represents a potential shortcoming for our cross-population analyses and not observations of antagonistic pleiotropy.…”
Section: Study Limitationssupporting
confidence: 84%
“…European populations, perhaps due to lesser linkage disequilibrium, as is consistent with results from previous studies [99]. Calculating disease risk and selection variation from populations within the same ancestral group might help resolve this, however it only represents a potential shortcoming for our cross-population analyses and not observations of antagonistic pleiotropy.…”
Section: Study Limitationssupporting
confidence: 84%
“…For example, the Duffy null allele is classified as a large-effect mutation using GERP (RS = 4.27) and is found at high frequency in western Africa; however, it has likely increased in frequency due to positive selection as a response to malaria (57). Recent genome-wide studies have stressed the paucity of selective sweeps in the human genome (35,58,59); only 0.5% of nonsynonymous mutations in 1000 Genomes Pilot Project were identified has having undergone positive selection. Others have emphasized evidence for pervasive adaptive selection (60,61) and a variety of studies have identified specific beneficial alleles locally adapted to high altitude, immune response, and pigmentation (62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
“…More generally, it has been observed that the geographic distributions of alleles under natural selection in humans tend to match the distribution of neutral population structure rather than any obvious geographic variation in selection pressures [105,106]. One factor contributing to this observation may be that selection pressures on individual loci are relatively weak due to the quantitative nature of phenotypes [107110].…”
Section: Scientific Opportunities For Ancient Dna Studiesmentioning
confidence: 99%